E-learning Program in Developing Performance Management and People Competency-Based System in Disruptive Era - Suksomjaipak, Arisa; Buaphuan, Chutinate; Kamolsuk, Nithipat (An Online Journal of Education, 2022)
The objectives of this research were to 1) develop an e-learning program for Performance Management and People Competency-Cased System in Disruptive Era and 2) assess e-learning programs on Performance Management and People Competency-Based System in Disruptive Era. The e-learning program’s users are human resource developers, administrators, human resource management students or those involved in the management and development of human resources, and media production specialists. Six people were selected using a specific method. The research tools were e-learning lessons, end-of-chapter exercises, interview forms, and satisfaction questionnaires with a 5-level estimation scale, The statistics used to analyze the data are the mean and the standard deviation. The research results are as below: 1) The result in the creation of an e-learning program based on the Analyze-Design-Develop-Implement-Evaluate (ADDIE) model yields 10 multimedia lessons, 1 summary, and 5 exercises at the end of each chapter. 2) Evaluation of the student’s program usage: The overall satisfaction average was high, with a mean of 4.09 and a standard deviation of 0.72. When all aspects were considered, it was found that the aspect that produced the most satisfaction was the use of the e-learning lessons (M = 4.3, SD = 0.692). The next most satisfying aspects were content (M = 4.2, SD = 0.772) and multimedia and transmission techniques (M = 3, SD = 0.72275), respectively.